2010
DOI: 10.1902/jop.2009.090414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metformin on Alveolar Bone in Ligature‐Induced Periodontitis in Rats: A Pilot Study

Abstract: Our findings suggest that metformin may exert a beneficial effect on alveolar bone in periodontitis by increasing osteoblast differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 38 publications
5
71
2
1
Order By: Relevance
“…Metformin administration significantly inhibited the progress of alveolar bone loss in the experimental groups after 28 days. These results confirm that of a recent study in which metformin was shown to directly inhibit bone loss in OVX rats and in rats with periodontitis (8,9). Enzyme histochemical observations indicated that the number of multinucleated osteoclasts in the periapical area in rats treated with metformin decreased at day 14.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Metformin administration significantly inhibited the progress of alveolar bone loss in the experimental groups after 28 days. These results confirm that of a recent study in which metformin was shown to directly inhibit bone loss in OVX rats and in rats with periodontitis (8,9). Enzyme histochemical observations indicated that the number of multinucleated osteoclasts in the periapical area in rats treated with metformin decreased at day 14.…”
Section: Discussionsupporting
confidence: 90%
“…Metformin significantly increases the alkaline phosphatase (ALP) activity and osteocalcin (OC) production and induces 2 key transcription factors for osteoblast differentiation (7). It also ameliorates bone loss in ovariectomized (OVX) rats (by regulating the activity of bone marrow cells) (8) and in ligature-induced periodontitis by promoting osteoblast differentiation (9).…”
mentioning
confidence: 99%
“…The osteogenic effect of metformin on osteoblasts has been reported by several groups [Cortizo et al, 2006;Kanazawa et al, 2008;Bak et al, 2010]. But little is known about the effect of metformin on osteoclasts.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report demonstrated that metformin prevented RANKL-induced osteoclasts differentiation in vitro [Gao et al, 2010]. However, study by Bak et al [2010] reported that metformin exerted no effects on osteoclast formation induced by VitD3, lipopolysaccharides, and prostaglandin E(2) (PGE 2 ). In this study, we confirmed that metformin inhibits osteoclast differentiation in a Raw264.7 cells and osteoblasts coculture system and in OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…Foi demonstrado também que a MET possui efeitos benéficos no metabolismo ósseo nos pacientes diabéticos (Vestergaard et al, 2005;Renjmark, 2008). Bak et al (2010) avaliaram os efeitos da MET sistêmica no osso alveolar em ratos com periodontite induzida, e os resultados sugeriram que o medicamento pode reduzir o infiltrado inflamatório e a perda óssea alveolar nos tecidos periodontais.…”
Section: Resultados Demográficosunclassified